High levels of circulating osteopontin in inflammatory lung disease regardless of Sars‐CoV‐2 infection. Issue 5 (31st March 2021) - Cappellano, Giuseppe; Abreu, Hugo; Raineri, Davide; Scotti, Lorenza; Castello, Luigi; Vaschetto, Rosanna; Chiocchetti, Annalisa
Abstract : This study independently confirms increased levels of osteopontin in COVID‐19 patients but also suggests that osteopontin cannot be used as a biomarker of SARS‐CoV‐2 infection, as elevated levels of circulating osteopontin are found in inflammatory lung disease regardless of SARS‐CoV‐2 infection.